2019
DOI: 10.3390/sports7070179
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Training Characteristics Associated with Atrial Fibrillation in Masters Runners

Abstract: A growing body of literature supports an association between long-term endurance exercise and the development of atrial fibrillation (AF). Given the benefits of lifelong exercise, a better understanding of this association is critical to allow healthcare providers to counsel aging exercisers on the proper “dose” of exercise to maximize health benefits but minimize AF risk. The current study examines the relationship between specific aspects of training volume and intensity and the occurrence of AF among older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…In this study the adjusted odds ratios per 10 years of regular endurance exercise were 1.16 (95% CI 1.06-1.29) for AF and 1.42 (1.20-1.69) for atrial flutter [102]. A recent study [103] focused on the potential impact of training characteristics on atrial arrhythmias in long-term endurance athletes. Based on multivariable analysis (adjusted for age), these authors identified accumulated training duration, but not specific training characteristics like frequency or intensity of endurance exercise, as the only significant predictor of AF [103].…”
Section: The Role Of the Overall Training Load And Participation Freq...mentioning
confidence: 59%
See 4 more Smart Citations
“…In this study the adjusted odds ratios per 10 years of regular endurance exercise were 1.16 (95% CI 1.06-1.29) for AF and 1.42 (1.20-1.69) for atrial flutter [102]. A recent study [103] focused on the potential impact of training characteristics on atrial arrhythmias in long-term endurance athletes. Based on multivariable analysis (adjusted for age), these authors identified accumulated training duration, but not specific training characteristics like frequency or intensity of endurance exercise, as the only significant predictor of AF [103].…”
Section: The Role Of the Overall Training Load And Participation Freq...mentioning
confidence: 59%
“…A recent study [103] focused on the potential impact of training characteristics on atrial arrhythmias in long-term endurance athletes. Based on multivariable analysis (adjusted for age), these authors identified accumulated training duration, but not specific training characteristics like frequency or intensity of endurance exercise, as the only significant predictor of AF [103]. AF was present in 14% of athletes reporting 0-10 years of running and in 44% of those reporting more than 30 years of running [103].…”
Section: The Role Of the Overall Training Load And Participation Freq...mentioning
confidence: 99%
See 3 more Smart Citations